The Distinction Influence of Booklet and Audiovisual Health Promotion Media on Knowledge and Attitude Of Prospective Bridegroom About Prevention of Hiv / Aids Invention in Religious Affairs Office of North Semarang (Public Health Perspective Journal, 2020)
Prevention of HIV / AIDS transmission by providing health promotion to prospective bridegroom is a promotive and preventive effort in preventing HIV transmission from sexual partners and mothers to their children. This study was aimed to analyze the differences in the effect of health promotion using booklet and audiovisual media in preventing HIV / AIDS transmission at the North Semarang Office of Religious Affairs. This type of research was a quasy-experimental study with a pre-test-post-test design. The sample of the study was 62 brides who were divided into 2 groups, 31 booklets and 31 audiovisual media. The analysis of this study uses the Wilcoxon Test and the Mann Whitney Test. The results showed that there was an influence of the booklet media on knowledge (p = 0,000) and attitudes (p = 0,000) to prospective bridegroom about the prevention of HIV / AIDS transmission. There is an increase in knowledge from the less (35.5%) to good (74.2%) category, while the attitude is from the (80.6%) to (93.5%). There is an influence of audiovisual media on the knowledge (p = 0,000) and attitudes (p = 0.001) of the prospective bridegroom on the prevention of HIV / AIDS transmission. An increase of knowledge from the moderate category (54.8%) to good (54.8%), while attitude is from (87.1%) to (96.8%). However there is no difference in the influence of booklet and audiovisual media on knowledge (p = 0.242 0.05) and attitudes (p = 0.104 0.05) of prospective bridegroom about preventing HIV / AIDS transmission.